Validation of a heat, moisture and gas concentration transfer model for soybean (Glycine max) grains stored in plastic bags (silo bags). (June 2017) - Arias Barreto, Alien; Abalone, Rita; Gastón, Analía; Ochandio, Dario; Cardoso, Leandro; Bartosik, Ricardo
Abstract : A two dimensional finite element model that predicts temperature distribution and moisture content of soybean stored in silo bags due to seasonal variation of climatic conditions is described. The model includes grain respiration and calculates carbon dioxide and oxygen concentrations during storage. The model validation was carried out by comparing predicted temperature, moisture content and gas concentration with measured data in field tests. Overall, the model underpredicted grain temperatures. Mean absolute difference was 0.5–1 °C for the bottom and middle layers and about 1.5 °C for the top layer. A slight moisture increase (0.4% w.b. at most) was predicted for the top grain layer while moisture for the middle and bottom layers remained almost unchanged during the storage period. A model of respiration rate of soybean as a function of temperature, moisture content and O2 level was used to predicted gas concentrations in the interstitial air. Average CO2 and O2 concentrations were compared with measured data. As mean grain temperature was below 15 °C for most of the storage period, O2 consumption and CO2 production were low. O2 level was about 19–20% V/V for dry soybean (13% w.b.) and about 16–17% V/V for wet soybean (15% w.b.). Predicted CO2 concentration varied from 1% V/V for dry soybean (13% w.b.) to 2% V/V points for wet soybean (15% w.b.). Though CO2 relative differences were high, the general trends of measured gas evolution were compatible with the simulated ones, indicating that the changes in CO2 and O2 concentrations during storage were satisfactorily predicted by use of the proposed correlations. Highlights: Validation of a heat and moisture model for soybean grains stored in silo bags. Soybean respiration modelled as function of temperature, moisture and O2 level. Validation of gas transfer model to predict gas concentration in a soybean silo bag.